Design of Reactor for The Production of PbO Particles - Vena, Tabita Dwi; Nandiyanto, Asep Bayu Dani; Ragaditha, Risti (Journal of Industrial and Engineering System, 2022)
The aim of this study was to design and analyze the batch reactor designs to produce PbO particles on an industrial scale. The method used in this research is to perform computational analysis and calculation of the reactor and its stirrer as well as the mass balance as the basis for calculations using the Microsoft Excel application. The study of reactor design is one of the key steps of a process design in industry, and these specifications are used as a reference in production costs. To produce PbO particles on an industrial scale (10,000× laboratory scale), are required two reactors and two stirrers. The calculation results show that the first reactor has a volume of 11.2334 ft3 with a height of 3.2219 ft and requires one stirrer with a power of 163 Hp, while the second reactor has a volume of 7.3576 ft3 with a height of 11.9503 ft and requires one stirrer with power 191 Hp. The results of this computation and analysis can be applied to the design and analysis of reactor performance as a learning medium and operating mechanism in a production system.